2013
DOI: 10.1155/2013/737264
|View full text |Cite
|
Sign up to set email alerts
|

The Sonodynamic Effect of Curcumin on THP-1 Cell-Derived Macrophages

Abstract: Curcumin is extracted from the rhizomes of the traditional Chinese herb Curcuma longa and has been proposed to function as a photosensitizer. The potential use of curcumin as a sonosensitizer for sonodynamic therapy (SDT) requires further exploration. This study investigated the sonodynamic effect of curcumin on macrophages, the pivotal inflammatory cells in atherosclerotic plaque. THP-1-derived macrophages were incubated with curcumin at a concentration of 40.7 μmol/L for 2 h and then exposed to pulse ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
2
40
1
Order By: Relevance
“…1,2 As the vital cells in unstable atherosclerotic plaques, macrophages participate in a maladaptive, nonresolving inflammatory response that expands the subendothelial layer due to the accumulation of cells, lipid, and matrix, which subsequently lead to the formation of vulnerable plaques. 2,3 Surgical treatment for AS, such as percutaneous coronary intervention, results in numerous complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 As the vital cells in unstable atherosclerotic plaques, macrophages participate in a maladaptive, nonresolving inflammatory response that expands the subendothelial layer due to the accumulation of cells, lipid, and matrix, which subsequently lead to the formation of vulnerable plaques. 2,3 Surgical treatment for AS, such as percutaneous coronary intervention, results in numerous complications.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) has emerged as one of the promising therapies in the treatment of cancers, and it is a type of noninvasive medical technology that consists of 1 O 2 ), which are produced as a result of the transfer of energy from an excited photosensitizer to adjacent oxygen molecules. 7 PDT has also been used to treat cardiovascular pathologies, including AS and restenosis, 8,9 and our group previously testified that 5-aminolevulinicacid-mediated PDT both decreases macrophage content and inhibits plaque progression in rabbit carotid artery AS models.…”
Section: Introductionmentioning
confidence: 99%
“…1 Macrophages play a pivotal role in atherogenesis, and the phenotype and quantity of these cells in atherosclerotic lesions influence both disease progression and plaque regression. 2 Photodynamic therapy (PDT) has been used to treat cardiovascular pathologies, including AS and restenosis, [3][4][5] which produces reactive oxygen species (ROS) and photo-induced biological damage according to the principle of energy transfer from light to a photosensitizer in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Our group demonstrated that emodin, curcumin, and 5-aminolevolinic acid (ALA) have sonodynamic effects in macrophages when combined with ultrasound by inducing apoptosis in vitro. 1,19,21 The polycyclic dione hypericin (HY), which is one of the active ingredients of St John's wort, is a photosensitizer that accumulates in dark glands found in flowers and leaves. [22][23][24] HY has been proposed as a highly promising photosensitizer due to its minimal toxicity, tumor high selectivity, high clearance from the host body, much singlet oxygen production and anti-inflammatory properties, as HY is able to induce the apoptosis of human lens epithelial cells, nasopharyngeal carcinoma cells, and U87 glioma cells 20,23,[25][26][27][28] during the rapid healing process after PDT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation